Domination Numbers Of Grids Mathematics subject classiﬁcation : 05C69 - Saood, Mahmod; Knefes, Kaled; Jobran , Jobran (Latakia University Journal -Basic Sciences Series, 2018)
This paper concerns the domination numbersfor the grid graphs for and for all. These numbers were previously established for.